The influence of a leadership model based on the book of Yoshua on the performance of Christian executive and legislative employees in Gurung Mas District, Central Kalimantan - Daliman, Muner; Bahan, Bambang; Suparti, Hana; Sugiyarto, Kristian Handoyo (Technium Social Sciences Journal, 2024)
One thing the world at this time needs is leadership. As a Christian, the bible contains countless figures who exhibit biblical leadership. In this day and age, Christian leadership is an uncommon and significant quality. Mrs. White even mentioned the traits of those who can stand up for what is right in the midst of chaos. Numerous individuals with this quality of leadership are mentioned in the Bible, including Joseph, Daniel, Paul, and even Jesus Christ, our Lord and Savior; however, the focus of this essay is Joshua, the man who succeeded. This paper is based on the identification results above, the researcher defines the problems that are considered to greatly influence the leadership model based on the book of Joshua on the performance of executive and legislative employees. This resultresultstesting of the hypothesis shows thatTransactional leadership based on the book of Joshuahas a positive and significant influenceOn the Performance of Christian executive and legislative employees in Gunung Mas Regency, Central Kalimantan Province.This is in accordance with the proposed hypothesis. Thus the hypothesis is declared accepted. Based on the T test, it is known that the t-count is 14.682 > t-table (14.682 > 1.654) and sig < 0.01 (0.000 < 0.01), this means that H0 is rejected and H6 is accepted. Or in other words shows thatTransactional leadership based on the book of Joshuahas a significant influence on the performance of Christian executive and legislative employees in Gunung Mas Regency, Central Kalimantan Province. From the Pearson correlation value on sub variablePerformance of Christian executive and legislative employees in Gunung Mas Regency, Central Kalimantan Province.